Presentation zen : simple ideas on presentation design and delivery - Reynolds, Garr, ....-; Kawasaki, Guy, 1954- (Berkeley : New Riders, 2012)
Presentation designer and internationally acclaimed communications expert Garr Reynolds, creator of the most popular Web site on presentation design and delivery on the net - presentationzen.com - shares his experience in a provocative mix of illumination, inspiration, education, and guidance that will change the way you think about making presentations with PowerPoint or Keynote. Presentation Zen challenges the conventional wisdom of making 'slide presentations' in today's world and encourages you to think differently and more creatively about the preparation, design, and delivery of your presentations. Garr shares lessons and perspectives that draw upon practical advice from the fields of communication and business. Combining solid principles of design with the tenets of Zen simplicity, this book will help you along the path to simpler, more effective presentations.
Keywords: Presentatietechnieken